(untitled) (Web of Teachers: Inderscience Research, 2025)
Human culture in society is very important, it is it that forms the biological individual and turns him into a social individual, thereby regulating and shaping his behavior. According to cultural scientists, “Each culture is a unique world created by a certain attitude of a person to the world and to himself. By studying different cultures, we not only study books, temples or archaeological finds, but also discover other human worlds in which people lived and felt differently from us. Each culture is a way of creative self-realization of a person. Therefore, understanding other cultures enriches us not only with new knowledge, but also with new creative experience” The book, the culture of reading (the culture of reading textual information) represents the initial and main factor in the formation of the entire culture. The culture of reading, the history of the emergence and development of books, is an integral part of the phenomenon of writing, reading culture, and the book is the most complete and diverse expression of the entire culture of mankind. The emergence and development of book products is closely related to the development of society.